Effects of the combination of cultivars and organic amendments for improving the resistance of water shortage in coffee - DOAN, Thuy; Mongchu, Chuthamat; Janeau, Jean L.; Maeght, Jean L.; Bottinelli, Nicolas; Le, Hao T.; Jouquet, Pascal (Asia-Pacific Journal of Science and Technology, 2021)
This study is aimed at studying the influence of organic fertilization on coffee growth and its resistance to drought. The experiment was carried out on young coffee plantlets in a greenhouse in Viet Nam and compared three varieties (Arabica L, Robusta TR9 and Robusta M38) and two types of organic amendments (compost or vermicompost). This study showed that both compost and vermicompost aided in the increase of soil chemical properties and above-ground plant biomass an as a comparison with chemical fertilizer. The vermicompost amendment has higher effect than compost could be observed for Arabica variety in term of soil organic carbon, total P, available N forms (N-NH4) except available K and shoot biomass weight (p<0,05), with no different between two Robusta varieties TR9 & M38 (p>0,05). Interestingly, the plantlets fertilized with organic amendments had lower (7 days) for resistance to drought than mineral chemical (9 days.) Therefore, these results suggest that the resistance of coffee plantlets to drought is reduced if the nursery growing media contains compost or vermicompost.